Scaring or scarring? Labour market effects of criminal victimisation - Anna Bindler; Nadine Ketel (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
Little is known about the costs of crime to victims. We use unique and detailed register data on victimisations and monthly labour market outcomes from the Netherlands and estimate event-study designs to assess short- and long-term effects of criminal victimisation. Across offences, both males and females experience significant decreases in earnings (up to -12.9%) and increases in benefit receipt (up to +6%) after victimisation. The negative labour market responses are lasting (up to four years) and accompanied by shorter-lived responses in health expenditure. Additional analyses suggest that the victimisation is a life-changing event leading to escalation points in victims' lives.
Keywords: K4; J01; J12; I1; 330; Crime; victimisation; labour market outcomes; event-study design